Academic Self-Efficacy of College Freshmen in Relation to English Language Competency - Galabasa, Nicolas N.; Vibal, Jobell Cris T.; Apohen, Sharon L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study is conducted to determine if academic self-efficacy and English language competency are correlated. Survey instruments on academic self-efficacy and English language competencies were administered to 221 college freshmen. Academic self-efficacy and English language competencies composed of vocabulary, grammar, and comprehension were determined using the mean, while the Kruskal Wallis test was used for differences and the Chi-square Test for relationships. Significant differences were evident in the level of academic self-efficacy and the level of English language competencies when grouped according to program enrolled and academic self-efficacy is significantly related to the English language competency of college freshmen. Future research will be conducted.